Development and Validation of a Coercive Control Measure for Intimate Partner Violence in Boston, Massachusetts and Washington, DC, 2004 - Dutton, Mary Ann ([Verlag nicht ermittelbar], 2008)
The overall goals of this project were to develop a clear theoretical understanding of coercive control and to develop a measure of "nonviolent coercive control" for use in the measurement of intimate partner violence (IPV). The psychometric properties of the newly developed coercive control measure were assessed between February and September 2004 in a total sample of 757 that included 302 males and 448 females from the metropolitan Washington, DC, and Boston areas. Of this sample, 139 reporting IPV victimization only, 39 reported IPV perpetration only, 245 reported both IPV victimization and perpetration, and 334 reported neither IPV victimization nor perpetration. Respondents were recruited from community agencies involving identified IPV victims and perpetrators, agencies providing non-IPV services to demographically similar participants, community college settings, and general public community settings, e.g., fast food restaurants. The sample was a convenience, not a representative, sample. Selection criteria included the following: (1) involvement in an intimate partner relationship within the past 12 months, and (2) being 18 years of age or older. Respondents were excluded if they exhibited signs of intoxication or other indications of a lack of coherence sufficient to complete the survey. Both data files contain demographic information. Respondents were asked several series of questions including those pertaining to demands received from their partner, whether their partner did anything to find out if the respondent had done what the partner had demanded, if their partner made them feel the partner might do something if the respondent did not do what the partner wanted, and whether they had done certain things when their partner demanded something. Respondents were then asked the same series of questions conversely. Respondents were read a statement and asked how often they felt this way in the past month, asked whether in the last 12 months they had experienced certain physical abuse or abused their partner physically, and they were asked whether in the last 12 months they had experienced certain types of emotional abuse or had abused their partner emotionally. Respondents were read a series of statements regarding their relationships with people in general and asked to tell whether the statement was true or false, asked how often they had experienced problems in response to a trauma, and asked how likely their partner might attempt to abuse the respondent in specific ways in the next year.